Eimeria acervulina Microneme Protein 3 Inhibits Apoptosis of the Chicken Duodenal Epithelial Cell by Targeting the Casitas B-Lineage Lymphoma Protein - Wang, Pu; Jia, Yukun; Han, Yue; Wang, Weirong; Zhu, Yiran; Xu, Jiali; Guan, Chiyu; Ying, Jinpeng; Deng, Simin; Wang, Jing; Zhang, Xian; Chen, Mianmian; et al. (Frontiers in Veterinary Science, 2021)
Eimeria acervulina (E. acervulina) causes coccidiosis in poultry which persists as economic pain worldwide. Most damage to the intestinal mucosa results from apoptosis of the infected intestinal epithelial cells. The Microneme protein 3 (MIC3) protein is a key virulence factor in some parasites involved in host cell apoptosis inhibition. Here, we studied whether and how MIC3 affects the apoptosis in E. acervulina infected chicken duodenal epithelial cells. Through flow cytometry (FCM), we found that the presence of merozoites and the overexpression of MIC3 significantly decreased apoptosis and the activity of caspase-3 in chicken duodenal epithelial cells at 4, 6, and 8 h post merozoite infection (P < 0.01). Silencing the Casitas B-lineage lymphoma (CBL) protein, a host receptor for MIC3 with shRNA was shown to promote apoptosis in the chicken duodenal epithelial cells. The early apoptotic rate of host cells in the lentiviral-MIC3 group was significantly lower than that in the lentiviral-MIC3 + shRNA CBL group at 4 h after MIC3 expression (P < 0.01), and it was moderately decreased in the lentiviral-MIC3 + shRNA CBL group compared with that in the shRNA CBL group. Our data indicated that MIC3 inhibited early apoptosis of E. acervulina infected chicken duodenal epithelial cells by targeting host receptor-CBL protein. These findings unveiled one of the mechanisms of how intracellular parasites affect the apoptosis of infected host cells, which provided a deeper understanding of their pathogenesis.